2021
DOI: 10.1108/ijoa-11-2020-2510
|View full text |Cite
|
Sign up to set email alerts
|

Overconfidence and credit risk-taking in microfinance institutions: a cross-regional analysis

Abstract: Purpose The purpose of this paper is to investigate the impact of loan officers’ overconfidence on risk-taking decision and solvency performance measured by z-scores in the context of Islamic and conventional microfinance institutions (MFIs). Design/methodology/approach A random effect generalized least square regression was applied to examine the effect of overconfidence on credit risk-taking. The data set covers 326 conventional MFIs and 57 Islamic MFIs in six different regions over the period of 2005–2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
1
2
0
1
Order By: Relevance
“…First, we observed that the size of MFIs has a significant negative effect on credit risk at the 1% level of significance. This finding is consistent with previous studies by Zamore et al (2019), Fersi and Boujelbène (2021), and Blanco‐Oliver et al (2021). Larger MFIs appear to have a competitive advantage in mitigating credit risk, as they can allocate more resources to risk supervision and monitoring.…”
Section: Discussionsupporting
confidence: 94%
“…First, we observed that the size of MFIs has a significant negative effect on credit risk at the 1% level of significance. This finding is consistent with previous studies by Zamore et al (2019), Fersi and Boujelbène (2021), and Blanco‐Oliver et al (2021). Larger MFIs appear to have a competitive advantage in mitigating credit risk, as they can allocate more resources to risk supervision and monitoring.…”
Section: Discussionsupporting
confidence: 94%
“…Managers can analyze financing above 100 million and above, but not necessarily staff can analyze the financing. Fersi and Boujelbène (2021) found overconfidence proxies have revealed negative repercussions on risk-exposures for both MFIs on average, as seen by high loan growth, low-interest margin, and loan loss provision. Overconfidence among loan officers is associated with a higher risktaking choice and, as a result, a lower loan portfolio quality.…”
Section: Risk Of Bmt Human Resources Capabilitymentioning
confidence: 89%
“…Además, no se registró ningún aumento en su capital social. Este fenómeno adquirió una relevancia considerable para el sector real, ya que facilitó la mejora de la liquidez y el fortalecimiento comercial de la entidad, sin la necesidad de acudir a terceros o de generar pasivos en la empresa como lo confirma (Fersi & Boujelbène, 2017) Fuente: Elaboración propia.…”
Section: Períodounclassified